THE ARCHETYPE OF PARADISE: DYING IN HOLIDAYS DOES NOT SOUND COOL - KORSTANJE, Maximiliano E (Revista de turism - studii și cercetări în turism, 2014)
Holidays play a vital role in the configuration of our life. Our most profound expectances are posed to this magic moment. However, under some contexts, what starts as a dream ends in a nightmare. It is unfortunate this is the case of victims of Villa Gesell’s tragedy, resulted when a ray impacted directly to a beach. Nobody is immune of tragedy, even at holidays. This essay review explores not only the anthropological roots of risk and paradise, but also the journalist discourse to cover the event. Far from the general opinion, disasters affect tourism, we strongly believe it strengths its attractiveness.